Development of Text Review Assessment Model Using Authentic Assessment in 11th Grade Students of Senior High School Negeri 1 Dolok Batunanggar, Simalungun Regency - Rizqa Jauhiratul Umma; Abdurahman Adisaputera; Isda Pramuniati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to analyze the development of a review text assessment model with authentic assessment in 11th grade students of Senior high school 1 Dolok Batunanggar Simalungun Regency. The subjects of this study were 11th grade students of Senior high school Negeri 1 Dolok Batunanggar, Simalungun Regency, and product validator experts totaling 4 people who had criteria as Indonesian Language material experts and assessment experts, namely authentic assessment. The results of this study indicate that the effectiveness of the authentic text assessment instrument review text obtained an average of 80.97%. The lowest student score is 70 and the highest is 98. This shows that student learning outcomes are better when compared to without the teacher using an authentic text review assessment tool. Based on the average value of students' posttest data it can be concluded that the ability of students has increased significantly high and reached KKM (72) as expected. It was concluded that the authentic assessment text review instrument developed was effectively used in learning.